2014
DOI: 10.1016/j.euromechflu.2013.12.001
|View full text |Cite
|
Sign up to set email alerts
|

2D axisymmetrical numerical modelling of the erosion of a cohesive soil by a submerged turbulent impinging jet

Abstract: International audienceThis study focuses on 2D Computational Fluid Dynamics (CFD) numerical modelling of the erosion of a cohesive soil by a circular impinging turbulent jet. Initially, the model is validated in the case of a non erodible flat plate. Several turbulence models are compared to experimental results and to simplified formulas available in the literature. The results obtained show that the Reynolds Stress Model (RSM) is in good agreement with the semi-empirical results in the literature. Nonetheles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This detailed study of the erosion threshold with the jet structure may be useful for a better understanding of the subsequent cratering beyond threshold where the shape modification of the surface affects the impingement flow structure, and could help for the validation of new numerical methods. 28,42 …”
Section: Discussionmentioning
confidence: 98%
“…This detailed study of the erosion threshold with the jet structure may be useful for a better understanding of the subsequent cratering beyond threshold where the shape modification of the surface affects the impingement flow structure, and could help for the validation of new numerical methods. 28,42 …”
Section: Discussionmentioning
confidence: 98%
“…To simplify the calculation process, this study focuses on the influence of impinging distance on the sand pit contour from a two-dimensional perspective, thereby reducing the computational workload [7][8][9]. The geometric model, as shown in Figure 1, consists of a tank measuring 0.9 m × 0.5 m, with a deposited sand height of 0.2 m. The nozzle, placed at the center of the model, has a diameter (D) of 3 mm, and the initial water level height (Z) is set at 0.5 m. The simulation duration is 20 seconds.…”
Section: Basic Assumptions and Modelsmentioning
confidence: 99%
“…Initial efforts combined CFD simulations for solving the JET hydrodynamics with erosion laws and adaptive remeshing for simulating the evolution of the water-soil interface. Mercier et al (2014aMercier et al ( , 2014b) implemented a combined Euler-Lagrange method that tracked the displacement of the soil-water interface as erosion progressed. Their findings showed that such a method can effectively model coupled changes in shear stress distribution and scour hole geometry.…”
Section: Jet Hydro-morphodynamic Numerical Modelingmentioning
confidence: 99%